2008
DOI: 10.1007/s10552-008-9166-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in prostate cancer survival in New Zealand: a national study

Abstract: Several possible explanations have been proposed to explain the survival disparities by ethnicity in New Zealand. Differentials in Gleason grade of disease by ethnic group explain a lot of these disparities. Further data on stage of disease at diagnosis, co-morbidity, treatment, access to health services, and behavioral and environmental factors are needed to resolve these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Mäori had a significantly poorer cancer survival rate than non-Mäori even after controlling for demographics or disease characteristics (see also Sneyd, 2008). Examination of the medical notes found that Mäori patients were significantly less likely than other ethnic groups to receive chemotherapy and were more likely to experience a delay of at least eight weeks before starting chemotherapy (Hill, Sarfati, Blakely, Robson, Purdie, Dennett, et al, 2010).…”
Section: Do Mäori Receive Poorer-quality Healthcare?mentioning
confidence: 97%
“…Mäori had a significantly poorer cancer survival rate than non-Mäori even after controlling for demographics or disease characteristics (see also Sneyd, 2008). Examination of the medical notes found that Mäori patients were significantly less likely than other ethnic groups to receive chemotherapy and were more likely to experience a delay of at least eight weeks before starting chemotherapy (Hill, Sarfati, Blakely, Robson, Purdie, Dennett, et al, 2010).…”
Section: Do Mäori Receive Poorer-quality Healthcare?mentioning
confidence: 97%
“…[9][10][11][12][13][14] There is clear evidence that Māori have poorer survival than other ethnic groups for most types of cancer. [9][10][11][12]14 (Pacific patients have poorer cancer survival compared with European patients, although their outcomes are somewhat better than those of Māori. 10 ).…”
Section: Inequalities In Cancer Outcomesmentioning
confidence: 99%
“…Māori experience a significant survival disadvantage for almost all the most common cancer sites (including lung, breast and colorectum), while Māori with cancers of the prostate or cervix are twice as likely to die from their disease compared with their European or non-Māori counterparts. 9,12,14 The exception to this pattern is melanoma, for which European patients have little or no survival advantage. 10,11,14 Why do Māori patients do worse?…”
Section: Inequalities In Cancer Outcomesmentioning
confidence: 99%
“…Prostate cancer (PCa) is the second leading cause of increased cancer incidence and cancer-related deaths among men in the United States [1], [2]. Despite treatment, the high mortality rates in PCa are attributed to metastasis, which is the main obstacle in PCa treatment [3].…”
Section: Introductionmentioning
confidence: 99%